Alternative Radio Stations and Ideological Propaganda in Zimbabwe: The Case of Voice of America’s Studio 7 - Jeffrey, Kurebwa; Mercy, Ndlovu (IJRDO - Journal of Social Science and Humanities Research, 2019)
The study explored the extent to which broadcasts from alternative radio stations contribute to spreading ideological propaganda with reference to Voice of America’s (VOA) Studio 7. Arguments on the nexus between the different ideologies and politics making radio in particular a contested space where politicians seek to project their version of reality and win support for themselves were presented. The study also outlined how alternative radio stations acted as the theatre where those on the periphery seek to subvert the status quo through creating a counter narrative challenging the existing order. Data was gathered through key informant interviews and documentary search. The major findings of the study were that the country’s restrictive media laws have resulted in the continued broadcast of Studio 7. Although such broadcasts are key in giving alternative voices, at times these are exaggerated hence tarnishing the country’s international image.